The evolution of human-type consciousness – a by-product of mammalian innovation mechanism – a preliminary hypothesis - Ben Zvi, Uzi (Frontiers in Psychology, 2025)
Human consciousness is often viewed as one of the pinnacles of evolution, with most theories positioning it as an upgrade of pre-existing cognitive skills. However, conscious perception, memory, action, and in some situations even decision-making, are often inferior—less complex, slower, and less accurate—than their nonconscious (subliminal) counterparts. The interface hypothesis challenges this perspective, proposing that human-type consciousness is not an advanced version of earlier cognitive capacities but a novel function that entered the arena of cognitive and operational processes and fundamentally changed its rules. According to this hypothesis, the neocortex emerged as part of an advanced innovation mechanism, where its unpredictable, chaotic activity is used to generate alternative patterns. The process of cropping these alternatives from the chaotic neocortex and mediating them to the constrained, goal-oriented, linear control system requires a serially functioning interface. Consciousness, it is suggested, arose as a byproduct or a side effect of this interface, eventually expanding its influence to a wide range of cognitive and operational functions. This perspective has significant implications for our understanding of human cognition, creativity, and the distinctive capacities of human consciousness, potentially bridging the gap between neuroscientific findings and phenomenological experiences of consciousness.